TECHNOLOGY TRANSFER; A PROBLEM OF BUYER-SELLER RELATIONSHIPS. - Indriyo Gitosudarmo (Journal of Indonesian Economy and Business (JIEB), 1994)
Technology transfer can be considered as a transaction between the two nations in the marketing of technology that needs dyadic motluations for relational exchange. Understanding the process of such exchange relationship between the supplier and receiver is of benefit in the situation that should be improved to encourage a better "buyer-seller relationship" between the two nations. This relationship has a strong effect to stimulate the trade through technology transfer between the supplier and recipient country. Marketers who understand that causal interaction and use it in decision-making have powerful ally in their battle for superiority in the market place